Reduced Quadriceps Motor-Evoked Potentials in an Individual with Unilateral Knee Osteoarthritis: A Case Report - Hunt, Michael A.; Zabukovec, Jeanie R.; Peters, Sue; Pollock, Courtney L.; Linsdell, Meghan A.; Boyd, Lara A. (Case Reports in Rheumatology, 2011)
One male with unilateral osteoarthritis (OA) of the knee underwent testing of corticospinal (CS) excitability (as quantified from motor-evoked potentials (MEPs) in the rectus femoris (RF) using transcranial magnetic stimulation) and quadriceps muscle strength. Baseline data indicated reduced MEP amplitudes in the RF of the affected limb compared to the unaffected limb. Increases in RF MEP amplitudes from both limbs were observed immediately following a 30-minute exercise session focusing on muscle strengthening. Following an 8-week muscle strengthening intervention, the participant exhibited increased MEP amplitudes and muscle strength in the affected limb. These findings suggest that alterations in peripheral muscle function found in patients with knee OA may have an origin centrally within the motor cortex and that interlimb differences may be evident in those with unilateral disease. These findings also suggest that CS excitability may be improved following a muscle strengthening intervention.